Harmonization of contract laws in ASEAN: Contract entropy - Nantanat Jintapitak (2018)
© 2017 American Scientific Publishers All rights reserved. This is the second part of the Harmonization of Contract Laws in ASEAN. This continuing research aims to compare and analyze the different contract laws of 10 ASEAN countries. The research is carried out by surveying and collecting data from Contract Laws in ASEAN. The appropriateness of the Model Basic Principles of ASEAN Construction Contract Law cannot be analyzed using the Standard Deviation (S.D.) which is one of statistical distribution tests. The researcher needed to find out a new possibility statistical distribution tests to analyze of appropriateness of the Model. The findings point to the possibility of applying Information-Theoretic Entropy in formulating the general principles of Construction Contract Law in order to measure the Probabilistic Uncertainty of Information in the form of a Consensus. However, the researcher would like to name such Information-Theoretic Entropy: “Contract Entropy.”.